Statistical anxiety and teacher presence among graduate students: A moderation analysis - Barcelona, Alvin B; Baraquiel, Jessica A; Cupo, Edalyn B; Ferreras, Eddieson T; Galarion, Charisma G; Yabut, Lea A; Zapanta, Jan Reino A (American Journal of Education and Learning, 2023)
Statistical anxiety is pervasive to a certain extent among graduate students and has been studied extensively in the literature. However, there seems to be a hiatus on what can moderate the relationship between anxiety and performance in statistics. The present study explored the moderating role of teacher presence in the statistical anxiety among 65 graduate students from three universities in the Philippines. The graduate students were found to have high levels of statistical anxiety in attending class, taking examination and in their computation self-concept while they have moderate levels of anxiety in asking for help, worth of statistics, and to their statistics instructors. There is sex difference in the statistical anxiety among the respondents with the male graduate students feel more negative in taking examination and attending statistics class, more afraid to ask help from others, and are less confident that they can succeed in their tasks than their counterparts. Meanwhile, teachers’ presence is assessed positively by the graduate students with their visibility very evident during direct instruction and assessment. This signifies teachers’ commitment to provide high quality instruction and assessment in their online statistics class. Also, the moderation analysis reveals that higher level of teacher presence is associated with weaker negative relationship between statistical anxiety while lower level of teacher presence is associated with stronger negative relationship between the two variables. The practical implications of this findings compel universities offering graduate programs to bolster teacher presence in statistics classes to ensure better learning experiences and outcomes among graduate students.